2013
DOI: 10.1007/s00380-013-0350-1
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus-related focal in-stent restenosis after everolimus-eluting stent implantation

Abstract: A 60-year-old man who had received repeated angioplasty for silent ischemia was suspected to have restenosis based on radioisotope imaging (exercise-RI) findings 6 months after everolimus-eluting stent (EES) implantation (3.5 × 28, 3.5 × 28, 3.0 × 18 mm). The stents had been implanted for chronic total occlusion of the right coronary artery (RCA), and the patient was on continuous dual antiplatelet therapy. Diagnostic angiography demonstrated in-stent restenosis in the proximal RCA, which was treated by optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This finding in association with IVUS and OCT images is different from that of ISR after BMS implantation, where intimal hyperplasia by smooth muscle cells occurs after BMS implantation [2]. Although, unfortunately, we did not perform plaque retrieval as a pathological specimen, white thrombus or inflammatory products or their complexes were possibly [3][4][5] present.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This finding in association with IVUS and OCT images is different from that of ISR after BMS implantation, where intimal hyperplasia by smooth muscle cells occurs after BMS implantation [2]. Although, unfortunately, we did not perform plaque retrieval as a pathological specimen, white thrombus or inflammatory products or their complexes were possibly [3][4][5] present.…”
Section: Discussionmentioning
confidence: 66%
“…Thus, SES ISR may be frequently associated with thrombus component. Hayashi et al [3] reported a similar phenomenon in a patient with ISR 6 months after everolimus-eluting stent (EES) implantation. Diagnostic angiography demonstrated focal ISR in the long multiple EESs.…”
Section: Discussionmentioning
confidence: 80%